Sedimentary environments and lithofacies distribution of zeit formation, red sea- Sudan - H.M.A.Eltayib, Sadam; M. Abdelrahman, El Sheikh.; S. M. Ibrahim, Ali.; A. O. Al-Imam, Omar (International Journal of Advanced Geosciences, 2019)
The Sudanese red sea coastal plain is geologically characterized by Cenozoic siliciclastic and shallow marine rift related sedimentary se-quences. Pliocene-Pleistocene is represented by the thick older gravel unit and the emergent linear reef terraces. In this study, wire line logs besides the investigations of cutting samples were used to investigate the un cored facies successions, to detect changes in grain size distribution, lithology and sedimentary facies and hence to interpret depositional environment. Confirmation of the log behavior using the cores and the cutting samples was undertaken. Furthermore, core to gamma-ray and spontaneous potential log correlations were set up. The lithofacies association and the depositional patterns of Zeit Formation were controlled by allocyclic and autocyclic processes, which include tectonic, palaeo climatic as well as depositional mechanisms. The lithofacies Distribution of Lower Zeit Member shows the southwestern part of the area is dominated by terrestrial to marginal marine partly supra tidal domain where some channel feeders can support the sand distribution from south to north. The central part of the area is dominated by shallow marginal marine to partly supra-tidal domains. The Middle Zeit Member was dominated by marginal marine to supratidal domain. The Upper Zeit Member repeated pattern of facies distribution being similar to that of Middle Zeit, however the sandy facies influxes increased towards the S. Suakin, Digna- area, towards Bashayer area and Durwara area from south to north.Â Â